anonymous
  • anonymous
6. Solve the equation. Show your work. Check your answer. 3x – 7 = 5x + 19 can someone help me with this
Algebra
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

misssunshinexxoxo
  • misssunshinexxoxo
Simplifying 3x + -7 = 5x + 19 Reorder the terms: -7 + 3x = 5x + 19 Reorder the terms: -7 + 3x = 19 + 5x Solving -7 + 3x = 19 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -7 + 3x + -5x = 19 + 5x + -5x Combine like terms: 3x + -5x = -2x -7 + -2x = 19 + 5x + -5x Combine like terms: 5x + -5x = 0 -7 + -2x = 19 + 0 -7 + -2x = 19 Add '7' to each side of the equation. -7 + 7 + -2x = 19 + 7 Combine like terms: -7 + 7 = 0 0 + -2x = 19 + 7 -2x = 19 + 7 Combine like terms: 19 + 7 = 26 -2x = 26 Divide each side by '-2'. x = -13 Simplifying x = -13
Kash_TheSmartGuy
  • Kash_TheSmartGuy
Simplifying 3x + -7 = 5x + 19 Reorder the terms: -7 + 3x = 5x + 19 Reorder the terms: -7 + 3x = 19 + 5x Solving -7 + 3x = 19 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -7 + 3x + -5x = 19 + 5x + -5x Combine like terms: 3x + -5x = -2x -7 + -2x = 19 + 5x + -5x Combine like terms: 5x + -5x = 0 -7 + -2x = 19 + 0 -7 + -2x = 19 Add '7' to each side of the equation. -7 + 7 + -2x = 19 + 7 Combine like terms: -7 + 7 = 0 0 + -2x = 19 + 7 -2x = 19 + 7 Combine like terms: 19 + 7 = 26 -2x = 26 Divide each side by '-2'. x = -13 Simplifying x = -13
anonymous
  • anonymous
Whoa your smart XD Thanks

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

misssunshinexxoxo
  • misssunshinexxoxo
Kash_TheSmartGuy
  • Kash_TheSmartGuy
Oh, I thought so, sorry :(
misssunshinexxoxo
  • misssunshinexxoxo
No worries, pleasure to meet you on OS
anonymous
  • anonymous
Thanks Kash
anonymous
  • anonymous
You're most welcome :) going to try to catch up to what you did there.

Looking for something else?

Not the answer you are looking for? Search for more explanations.